FRI0045 Therapeutic Blockade of Interleukin-6 Trans-Signalling Restores Vascular Function in Murine Collagen Induced Arthritis. (15th July 2016) - Davies, R.; Williams, J.; Sime, K.; Hughes, E.; Jordan, L.; Rawlings, C.; Lang, D.; Jones, S.; Rose-John, S.; Williams, A.; Choy, E.
Abstract : Background: Mortality is increased in rheumatoid arthritis (RA), mainly due to cardiovascular disease (CVD). While molecular mechanisms underlining this observation are unknown, systemic elevations in inflammatory cytokines, eg interleukin (IL)-6 frequently correlate with increased cardiovascular risk. IL-6 plays roles in both immune homeostasis and driving chronic disease progression. Control of these processes is regulated by two modes of IL-6 signalling; classical IL-6 signalling and IL-6 trans-signalling. Cellular responses controlled by IL-6 trans-signalling are mediated via soluble IL-6 receptor (sIL-6R) and is widely considered to promote pro-inflammatory outcomes. Importantly, a genetic polymorphism within IL6R enhances circulating sIL-6R level and is associated with CVD incidence in the general population. Biological drugs against IL-6 or IL-6R block both classical and trans-signalling. However it is advocated that selective inhibition of IL-6 trans-signalling may reduce clinical complications associated with a more global intervention strategy. Murine collagen induced arthritis (mCIA) is associated with vascular dysfunction, with reduced aortic constriction to 5-HT. Here, we found systemic alterations in vascular tone, as a response to mCIA, was attributable to IL-6 trans-signalling. Objectives: Investigations assessed whether inhibition of IL-6 trans-signalling using the selective antagonist sgp130Fc affected aortic constriction as an index of vascular dysfunction in mCIA. Methods: Arthritis was induced in 8 week old male DBA/1 mice by type-II collagen, as previously described 1 . Animals were administered IV sgp130Fc (2.5mg/kg) or PBS weekly from day 21. Arthritis severity was monitored daily from day 21–30. Vasoconstriction of aortic rings in response to 5-HT was monitored as an index of vascular function using isometric tension myography. Results are expressed as mean ± SEM (n=10). Results: When compared with PBS controls (Arthritis Index:4.3±1.1), disease severity was significantly ( P <0.05) reduced in sgp130Fc (1.5±0.6) treated mice (Fig1 A). PBS control mice with mCIA had reduced vasoconstriction (developed tension 8.5±0.6mN for non-immunised mice, 5.8±0.8mN for mCIA mice; P <0.05). Significantly, improvement of disease activity observed for sgp130Fc treated animals was associated with normalisation of vascular function (developed tension 8.1±0.6mN). Conclusions: Consistent with previous reports 1, sgp130Fc reduced arthritis in mCIA. Sgp130Fc also restored vascular function. Selective IL-6 trans-signaling blockade by sgp130Fc is a promising therapeutic strategy for both RA and its associated CVD. Further work is needed to elucidate the role of IL-6 trans-signaling in pathogenesis of vascular dysfunction in mCIA and RA. References: Nowell MA, Williams AS, Carty SA, Scheller J, Hayes AJ, Jones GW, Richards PJ, Slinn S, Ernst M, Jenkins BJ, Topley N, Rose-John S, Jones SA. Therapeutic targeting of IL-6 trans signaling counteracts STAT3 control of experimental inflammatory arthritis. J Immunol. 2009 Jan 1;182(1):613–22. Acknowledgement: Dr Ruth Davies is supported by an Arthritis Research UK Clinical Fellowship. CREATE Centre is funded by Arthritis Research UK & Health and Care Research Wales. Disclosure of Interest: None declared